INVESTMENT STRATEGY, BUSINESS CAPITAL AND INCOME AGAINST RECESSION RISK THROUGH GOVERNMENT REGULATIONS IN THE CONTEXT OF ACHIEVING SDG'S NO. 9 - Supardi; Sriyono; Lisa, Oyong (PT. Antis International Publisher, 2024)
Objective: This study examines the relationship between investment methodology, working capital, and income in the context of recessionary uncertainty. It specifically explores the role of government regulations in advancing Sustainable Development Goal (SDG) No. 9, focusing on industrial innovation, infrastructure, and resilience. Method: The investigation employs an explanatory and scientific approach, integrating theoretical and empirical analysis to assess the interactions between investment strategies, working capital, income, and government regulations during economic downturns. Data are analyzed to evaluate the mediating effects of government regulation on these variables. Results: The findings indicate that investment strategies targeting critical infrastructure foster durable economic expansion, enhancing resilience during recessions. Flexible working capital management mitigates market instability risks. The results reveal that investment strategies and income significantly influence government regulation, while enterprise capital does not. Additionally, investment strategies and venture capital impact recession risks indirectly through government regulation, which also mediates the influence of income on recession risk. Novelty: This study uniquely highlights the mediating role of government regulation in linking income and recession risk, as well as its impact on investment strategies and venture capital. By aligning these insights with SDG No. 9, it contributes to the broader understanding of how economic policies and private sector strategies can collaboratively enhance resilience during economic downturns.